ANALISIS KOREOGRAFIS SAMRAH DI PONDOK PESANTREN AL-KHAIRAAT BUNTULIA KABUPATEN POHUWATO - Fingki Yaningsi Ruiba; Riana Diah Sitharesmi; Trubus Semiaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Samrah is a form of dance-based art that thrives in various Gorontalo communities, including at Al-Khairaat Buntulia Islamic Boarding School. Samrah is a type of religious performance art that combines elements of movement, music, lyrics, and costume to express Islamic values. This study employed a descritive qualitattive approach. Data collection techniques included direct observation at Al-Khairaat Buntulia Islamic Boarding in Pohuwato Regency, interviews with educators,, dancers, and members of the local Arab-descendant community, as well as documentation. The choreographic analysis focused on movement structure, floor petterns, number of dancers, musical accompaniment, costumes, and tthe meanings embedded in the performance. Tthe results showed tthat the Samrah choreography at Al-Khairaat Buntulia Islamic Boarding School is dominated by footwork movements, foot stomping, swinging arm movements, hand clapping, and turning movements. The floor patterns tend to be symmetrical and repetitive, reflecting the values of ukhuwah islamiyah (Islamic brotherhood) and equality among the dancers. Moreover, the interrelation between movement, music, and lyrics positions Samrah not only as a performing art from but also as an educational medium and a means of implementing Islamic values within the Islamic boarding school environment. This study is expected to contribute to the study of traditional performing arts, particularly in the context of Islamic boarding school education and the preservation of local culture grounded in raligious values.